Comparative Study between Drug and Plant Extract for Treatment of Diabetes in Rats - Daibes, Zahra'a (American Journal of Biology and Natural Sciences, 2025)
The present study was designed for knowledge the comparative study between drug and plant extract for treatment of Diabetes in rats. Cashew that had fully developed and dried in the shade were gathered, cleaned, and crushed into a coarse powder. Using a Soxhlet extractor and ethanol, extracts was done. STZ was administered once at a dosage of 70 mg/kg body weight for the induction of DM. For rats that had been fasting overnight, intraperitoneal injections were utilized, and all treated rats were given access to food and drink. Additionally, fasting blood glucose levels were calculated after 4 days of stabilization for the rats. As a diabetic model, rats with glycemia levels higher than 17 mmol/L were used in the study. Forty adult male rats were used in this study, these were divided into 4 groups. G1 negative control, G2 given STZ only (positive control), G3 given STZ and then treated by Glimepiride (5 mg/10 ml)+ Atorvastatin 10 mg/kg , G4 given STZ and then treated by Cashew extract at 100 mg/kg. Rats were fasted for eight hours after five weeks. Diethyl ether was used to anesthetize the rats, and blood samples were taken at days 0,7,14,21. The serum samples were maintained at -80°C after the blood serum was separated. The levels of a few biochemical parameters, such as glucose, the lipid profile as well as liver function tests (ALT and AST) which purchased from Biolabo company. More significant (p < 0.05) anti-diabetic activity was observed for drugs and cashew extracts, which shows significant gradual decrease in blood glucose levels, TG, C, AST and ALT in both G3 and G4, while HDL was increase significantly after treatment with drugs and cashew extract. In conclusion, cashew have significant role in control of diabetes by decreasing blood glucose levels, TG, C, AST and ALT and increasing in HDL.